Optimisme dengan Adversity Quotient pada Siswa Kelas XII SMA Kartika Padang - Purwanti Endah Rahayu; Frihapma Semita Ade; Hendri Gunawan (Departement of Mathematics Education, 2023)
Adolescence is an important period in the life span, a period in which individuals experience changes, namely a transition period from children to adults, cognitive, physiological, and socio-emotional changes . At this time adolescents face many problems related to education in schools, learning activities are the most basic activities for students, but these learning activities for each student do not always run smoothly according to what they want. This study aims to see the relationship between Optimism and Adversity Quotient in Class XII students of SMA Kartika Padang. The measuring instrument used in this scale is the scale of optimism and Adversity Quotient. The sampling technique in this study used the Simple Random Sampling technique. The sample in this study were 130 students of SMA Kartika Padang. Test the validity and reliability in this study using the Cronbach Alpha analysis technique. The results of the validity coefficient on the optimism scale move from rix = 0.322 to rix = 0.609 with a reliability coefficient of = 0.899 while the results of the validity coefficient on the Adversity Quotient scale move from rix = 0.409 to rix = 0.900 with a reliability coefficient of =0.976. Based on data analysis, obtained a correlation value of 0.787 with a significance level of 0.000 (p<0,05), which means the hypothesis is accepted. Research shows that there is a significant relationship between optimism and Adversity Quotient in Kartika Padang High School Students.